Development of Candida autochthonous starter for cigar fermentation via dissecting the microbiome - Jia, Yun; Liu, Yuanfa; Hu, Wanrong; Cai, Wen; Zheng, Zhaojun; Luo, Cheng; Li, Dongliang (Frontiers in Microbiology, 2023)
To clarify the influence of microbes on cigar quality, this study revealed the succession of microbial community structure and physicochemical metabolites during cigar leaf fermentation by high-throughput sequencing and metabolomics. The results showed that the relative abundance of Staphylococcus and Aspergillus increased first but then decreased during the fermentation, and would occupy the dominant position of bacterial and fungal communities respectively on the 21st day. Correlation analysis predicted that Aspergillus, Staphylococcus and Filobasidium could contribute to the formation of saccharide compounds, Bacillus and might have degradation effects on nitrogenous substances. In particular, Candida, as a co-occurring taxa and biomarker in the later stage of fermentation, could not only degrade nitrogenous substrates and synthesize flavor substances, but also contribute to maintaining the stability of microbial community. Moreover, based on in vitro isolation and bioaugmentation inoculation, it was found that C. parapsilosis and C. metapsilosis could significantly reduce the alkaloids content and increase the content of flavor components in tobacco leaves. In general, this study found and validated the critical role of Candida in the fermentation of cigar tobacco leaves through high-throughput sequencing and bioaugmentation inoculation, which would help guide the development of microbial starters and directional regulation of cigar tobacco quality.